The Vulnerability of Cameroonian Employees in the Midst Of Health Crisis: The Right of Employment Sacrificed On the Alter of Corporate Rescue (African Journal of Law and Politics, 2023)
The law has provided a mechanism which permits employers to reduce the hardship which unfavorable economic conditionscan impose on the enterprise by permitting them to either terminate or suspend their contracts with employees in order to reduce the burden imposed by the payment of salaries, on condition however that a minimum is done to protect the employees. But the unfortunate and sad reality is that employers hardly consider these minimum requirements for employee protection and frequently execute the layoff or dismissal of employee agenda on a unilateral basis without associating the different stakeholders. The employees are thus very vulnerable when an enterprise is hit by economic crisis be it imposed by a health hazard like Covid19 or coming from some other direction. Under the Cameroonian Labour Code, sections 32(k) and section 40 have given the employers power to temper with their contractual obligations with employees. In application of these sections corporate employees find themselves either negotiating for a layoff or dismissal. Either way the pill is a bitter one to swallow. This paper seeks to investigate on the measures put in place by the Cameroonian legislator to guarantee the rights of employees during a crisis period such as the present Corona Virus pandemic plaguing the globe for several months now. Our findings have led to the conclusion that in crisis periods, the Cameroonian Labour Code for pragmatic reasons places the employee in a very vulnerable position vis-a-vis the employer .Nevertheless it outlines certain measures that must be followed if any employee is to be placed on technical unemployment or any dismissal based on economic grounds. We regret the fact that in application of the above provision during crisis period, most employees are either laid off or dismissed based on the above mentioned Sections without due process of law. The paper ends up with some recommendations that if adopted, will place the workers in more favourable conditions in situations of crisis.